Foundation studies for cadmium accumulation studies in terrestrial isopods - diet selection and diet contamination - Mann, Reinier M.
Food palatability studies were carried out with the terrestrial isopods Porcellio dilatatus and Porcellinoides pruinosus. They were provided with leaves of lettuce (Lactuca sativa), pea (Pisum sativum), Elodea and alder (Alnus glutinosa) to determine their suitability as food substrates for metal accumulation tests with these isopods. Lettuce, pea and Elodea were also assessed for their ability to take up cadmium in hydroponic culture. In the feeding trials, growth, consumption and assimilation indices indicated that lettuce may be a suitable food, while the plant contamination trials indicated that lettuce and Elodea could take up large quantities of cadmium into the leaves. These studies form part of a project to develop a system for delivering metal contaminants to terrestrial isopods for metal accumulation studies that incorporate the principles of trophic transfer. (c) 2005 Elsevier SAS. All rights reserved.